Corruption and Legitimacy - Zulkarwin Zulkarwin (Journal of Governance, 2021)
The term of legitimacy is always central in the political discussion around the globe. The contested explanations about legitimacy regarding the types and the way it is obtained are widely discussed and analyzed including the causes of the crisis of legitimacy and how to maintain the legitimacy. Nevertheless, legitimacy will be in critical if the governed start to probe whether that conferring power is exercised in the right way or not. One of the prominent causes of crises legitimacy is corruption. The venal actors in the legitimate states are often assumed to deteriorate the legitimacy of the countries. This essay, therefore, aims to discuss the impact of corruption toward states’ legitimacy. The discussion of this essay is conducted through library research of some relevant journals and related publications. It evident that corruption affects the political legitimacy which acts as a foundation of political authority.Keywords: legitimacy; corruption; governance; political authority.